Experimental studies on elastic properties of high density polyethylene-multi walled carbon nanotube nanocomposites - Fattahi, A. M.; Safaei, Babak; Qin, Zhaoye; Chu, Fulei (Techno-Press, 2021)
The effect of nanoparticle volume fraction on the elastic properties of a polymer-based nanocomposite was experimentally investigated and the obtained results were compared with various existing theoretical models. The nanocomposite was consisted of high density polyethylene (HDPE) as polymeric matrix and 0, 0.5, 1 and 1.5 wt.% multi walled carbon nanotubes (MWCNTs) prepared using twin screw extruder and injection molding technique. Nanocomposite samples were molded in injection apparatus according to ASTM-D638 standard. Therefore, in addition to morphological investigations of the samples, tensile tests at ambient temperature were performed on each sample and stress-strain plots, elastic moduli, Poisson?s ratios, and strain energies of volume units were extracted from primary strain test results. Tensile test results demonstrated that 1 wt.% nanoparticles presented the best reinforcement behavior in HDPE-MWCNT nanocomposites. Due to the agglomeration of nanoparticles at above 1 wt.%, Young?s modulus, yielding stress, fracture stress, and fracture energy were decreased and Poisson?s ratio and failure strain were increased.
Keywords: high density polyethylene; multi walled carbon nanotubes; elastic properties; experimental investigation